Kol (Purn). SB. Mansoersami Prajurit Gyugun Sumatera Barat - Dedi Asmara; Reno Henriko (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2020)
This research aims to study the history of the Indonesian military which has a long and winding journey. (Pur). SB. Mansoersami is one of those little people. Only has a few important letters and documents that prove that he had been a soldier during the Japanese government. This research uses historical research methods in the form of; heuristics, where all sources are collected, both oral and written. Then criticism is carried out to test the truth which will produce valid facts and data. Finally only interpreted as writing (historiography). The results of this study that the history of Col. (Pur). SB. Mansoersami was born from the descendants of the Sultanate of Siak Inderapura. Began to get the world of education from the People's School and at the time of the Japanese occupation took military education in Gyugun. The conclusion of this research is that the history of Captain (Ret) Mansoersami begins from the time he saw A. Talib returned home to the village dressed in military uniform complete with a samurai sword that looked dashing, so that made him enter into Gyugun Keywords: Gyu Gun, Military, Japan.